Water availability and demand in the Sorocaba river watershed, Brazil: an alert to the management of water resources - Abreu, Marcio Costa; Tonello, Kelly Cristina (Sociedade & Natureza, 2018)
We aimed to contribute to the understanding of the dynamics of water resources in the Sorocaba river watershed and to elucidate the relationships between water supply and water demand therein, thereby providing subsidies for governmental action plans. Water supply was calculated by the Q95% of the time in the studied series at the basin mouth. The flows of each consumptive demand were obtained from data on the permit-granting processes, by different methods. The demands for human consumption (urban and rural populations), animal feed, industrial use and irrigation were calculated. The demands were estimated at 11.86 m³.s-1, with the highest flow for human supply (6.20 m³.s-1), followed by irrigation (3.59 m³.s-1) and industrial (1,83 m3.s-1), corroborating with the urban and industrial characteristics of the basin. The current demand in the basin corresponds to 49% of the water availability based. Such relationship between supply and demand indicates that the basin is at a highly critical state regarding the use of its water resources, thus showing potential for the occurrence of conflicts. The situation is even worse when we consider water quality issues, which were not object of our study, yet would certainly restrain water availability for certain uses.